Here and there sites of philosophy - Cavell, Stanley 1926-2018 (Harvard University Press, 2022)
"Stanley Cavell was one of the most distinguished and wide-ranging philosophers of his time. This posthumous volume assembles an array of writings that Cavell left behind, synthesizing into a cohesive intellectual vision unpublished works on modernity, music, skepticism, psychoanalysis, anthropology, tragedy, and the human voice"--
Keywords: Philosophie; Philosophy, Modern; Criticism (Philosophy); Psychoanalysis and philosophy; Aufsatzsammlung